Swinholide J, a Potent Cytotoxin from the Marine Sponge Theonella swinhoei - De Marino, Simona (Molecular Diversity Preservation International, 2011)
In our ongoing search for new pharmacologically active leads from Solomon organisms, we have examined the sponge Theonella swinhoei. Herein we report the isolation and structure elucidation of swinholide A (1) and one new macrolide, swinholide J (2). Swinholide J is an unprecedented asymmetric 44-membered dilactone with an epoxide functionality in half of the molecule. The structural determination was based on extensive interpretation of high-field NMR spectra and HRESIMS data. Swinholide J displayed potent in vitro cytotoxicity against KB cells (human nasopharynx cancer) with an IC(50) value of 6 nM.